Experimental Analysis of the Accessibility of Drawings with Few Segments - Kindermann, Philipp; Meulemans, Wouter; Schulz, André (Journal of Graph Algorithms and Applications, 2018)
The visual complexity of a graph drawing is defined asthe number of geometric objects needed to represent all its edges.In particular, one object may represent multiple edges, e.g., one needsonly one line segment to draw two collinear incident edges.We investigate whether drawings with few segments have a better aesthetic appeal and help the userto assess the underlying graph.We design a user study that investigates two different graph types(trees and sparse graphs), three different layout algorithms for trees, andtwo different layout algorithms for sparse graphs. We asked the participants togive an aesthetic ranking on the layouts and to perform a furthest-pair or shortest-path task on thedrawings.